Clinical phenotype and genetic analysis of patients with severe oligoasthenospermia carrying heterozygous SOHLH1 c.346-1G>A mutation - Wen, Xiaojun; Li, Zhiming; Cheng, Lizi; Wei, Jianhong; Yu, Wenjuan; Lin, Xiufeng; Fang, Xiaowu (Frontiers in Genetics, 2025)
IntroductionSevere oligoasthenospermia (SOA) is a prevalent cause of male infertility. However, the underlying causes of most SOA cases remain unclear due to the complexity of germ cell development and the significant genetic heterogeneity associated with male infertility. Therefore, in this study, we aimed to elucidate the genetic etiology of two cases of male infertility resulting from SOA and clarify the novel clinical phenotype associated with a heterozygous mutation at the c.346-1G>A site of the SOHLH1 gene.Methods and resultsThrough whole-exome sequencing, we found that patients with SOA carried heterozygous mutations at the c.346-1G>A site. This variant is classified as pathogenic based on disease database records and literature reports. Notably, our study demonstrated that patients with heterozygous mutations at the c.346-1G>A site exhibited severely reduced sperm counts, significantly impaired sperm motility, and pronounced morphological deformities. One patient underwent assisted reproductive treatment through an intracytoplasmic sperm injection and achieved a favorable outcome, resulting in a successful pregnancy.DiscussionIn conclusion, our study provides the first evidence that the heterozygous mutation at the c.346-1G>A site of SOHLH1 is associated with SOA, and elucidates the new clinical phenotype associated with this mutation.